Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T20:55:43+01:00
A)
x+3y=3
x-y=5

x+3y=3
x=5+y

5+y+3y=3
x=5+y

4y=3-5
x=5+y

4y=-2
x=5+y

y=-½
x=5+(-½)

y=-½
x=4½
-------------------
b)
3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11

n=9-3m
2m-45+15m=-11

n=9-3m
17m=-11+45

n=9-3m
17m=34

n=9-3m
m=2

n=9-3*2
m=2

n=3
m=2
------------------
c)
5x=4-2y
4x+y=3

5x=4-2y
y=3-4x

5x=4-2(3-4x)
y=3-4x

5x=4-6+8x
y=3-4x

5x-8x=-2
y=3-4x

-3x=-2
y=3-4x

x=2/3
y=3-4*2/3

x=2/3
y=1/3
2009-12-07T21:01:24+01:00
A
x+3y=3
x-y=5
x = 3 - 3y
3 - 3y - y = 5
3 - 4y = 5
- 4y = 5 - 3
- 4y = 2
y = - 2/4 = - 1/2
x - y = 5
x + 1/2 = 5
x = 5 - 1/2 = 4 i 1/2
b
3m+n=9
2m-5n=-11
n = 9 - 3m
2m - 5(9 - 3m) = - 11
2m - 45 + 15m = - 11
17m = - 11 + 45
2m = 34
m = 17
3m + n = 9
3 razy 17 + n = 9
51 + n = 9
n = 9 - 51 = - 42
c
5x=4-2y
4x+y=3
y = 3 - 4x
5x = 4 - 2(3 - 4x)
5x = 4 - 6 + 8x
5x - 8x = - 2
- 3x = - 2
x = 2/3
4x + y = 3
4 razy 2/3 + y = 3
8 + 3y = 9
3y = 9 - 8
3y = 1
y = 1/3
2009-12-07T21:01:50+01:00
A).
x+3y=3
x-y=5

x+3y=3
x=5+y

5+y+3y=3
x=5+y

4y=3-5
x=5+y

4y=-2
x=5+y

y=-0,5
x=5+0,5

x=5,5
y=-0,5

b).
3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11

n=9-3m
2m-45+15m=-11

n=9-3m
17m=34

n=9-3m
m=2

n=9-3*2
m=2

m=2
n=4

c).
5x=4-2y
4x+y=3

5x=4-2y
y=3-4x

5x+2(3-4x)=4
y=3-4x

5x+6-8x=4
y=3-4x

-3x=-2
y=3-4x

x=3/2
y=3-4(3/2)

x=3/2
y=3-6

x=3/2
y=-3